Transmuted Survival of Lindley Distribution (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:In this study, a new distribution was discovered as a survival model by utilising the survival function of the quadratic-transformed distribution, where the quadratic-transformed Lindley distribution was used to derive the transformed-as-survival (TSL) Lindley distribution, which is essential because it is more flexible and accurate in data applications. Since there are occasionally data points that do not meet the standard distribution, the new distribution provides more accurate results when applied to the data, and the probability density function and cumulative probability function are extracted. New deployment properties with reliable performance were derived from a statistical and mathematical perspective. We also estimated a dataset using traditional methods, and we utilized MATLAB to demonstrate that our new distribution is superior to the original.Materials and Methods:The researchers also estimated a datum set using the Maximum  Likelihood Estimators method, and it manifested  the excellence of our Transmuted Survival of Lindley Distribution compared to the Lindley DistributionResults:                                                                 The results that the researchers obtained indicated that the new distribution(TSLD) is better than the original distribution . The  distribution of the New GLD for this real data in table (1).Conclusion:In this research, the formula Transmuted Survival  and Lindley  distribution are used and  the obtained result has more efficient distribution than the original distribution.